2012
DOI: 10.1371/journal.pone.0040814
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Nonmuscle Myosin II in Assembly of the Cellular Contractile System

Abstract: The contractile system of nonmuscle cells consists of interconnected actomyosin networks and bundles anchored to focal adhesions. The initiation of the contractile system assembly is poorly understood structurally and mechanistically, whereas system’s maturation heavily depends on nonmuscle myosin II (NMII). Using platinum replica electron microscopy in combination with fluorescence microscopy, we characterized the structural mechanisms of the contractile system assembly and roles of NMII at early stages of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 92 publications
17
109
0
Order By: Relevance
“…Part of this is due to the crowded nature of the cytoskeleton, which makes it difficult to distinguish the small myosin filaments from the other elements, and part of this is due to difficulties in preserving their structures. Nevertheless, the images of filaments that are available bear a strong resemblance in size and shape to the in vitro filaments presented here (72,74,77). Of additional interest is the resemblance of the ribbon-like structures that we find at slightly lower ionic strength where the myosin filaments interact in both a head to head manner and in a parallel stacking arrangement.…”
Section: Paralogmentioning
confidence: 52%
See 1 more Smart Citation
“…Part of this is due to the crowded nature of the cytoskeleton, which makes it difficult to distinguish the small myosin filaments from the other elements, and part of this is due to difficulties in preserving their structures. Nevertheless, the images of filaments that are available bear a strong resemblance in size and shape to the in vitro filaments presented here (72,74,77). Of additional interest is the resemblance of the ribbon-like structures that we find at slightly lower ionic strength where the myosin filaments interact in both a head to head manner and in a parallel stacking arrangement.…”
Section: Paralogmentioning
confidence: 52%
“…In the cell, actomyosin networks are arranged in a variety of different geometries. These include sarcomeric structures such as those seen in stress fibers and purse strings as well as less ordered networks such as those seen at the peripheral region of the lamella (72)(73)(74). Because of the splaying and flexibility of individual NM II molecules from the filament, the actomyosin interactions seen here occur over a wide range of geometries, explaining how NM II filaments can maintain interactions with actin in the absence of well ordered sarcomere-like structures.…”
Section: Paralogmentioning
confidence: 87%
“…17,18,37 In accordance with this hypothesis, we observed that the spatial organization of F-actin is abnormal in Myh9 2/2 MKs and actin polymerization is decreased in these platelets, indicating a role of myosin IIA in F-actin dynamics in MKs. The involvement of myosin II in actin polymerization/structuration has already been documented for F-actin cross-linking 38,39 or for catalyzing actin assembly at focal adhesions 39 or in dynamic structures where rapid actin filament turnover is required. [40][41][42] Thus, myosin IIA is likely to contribute to organelle distribution by organizing the actin meshwork necessary for organelle tethering and transport.…”
Section: Discussionmentioning
confidence: 97%
“…This difference in the effect of the two inhibitors on endosomal size might, however, be explained by the different mechanisms of action of the drugs because ML7 and Y27632, but not blebbistatin, interfere with phosphorylation of myosin II Shutova et al, 2012).…”
Section: Rab7b Transport Is Dependent On Myosin IImentioning
confidence: 99%